Prescrição automatizada de cadeira de rodas do atletismo paralímpico - Donegá, Thiago José (2020)
Wheelchair racing is one of the most traditional modalities of paralympic athletics. This sport is practiced by individuals with polio sequelae, spinal injuries and amputations. From its beginnings to present day, wheelchairs used in races have gone through the several structural changes that have maximized the science of athletes in this sport. In general, these chairs are customized according to the athletes' ergo-anthropometric conditions, and this is done from pre-established dimensions by manufacturers, available in their manuals. In general, the athletes choose the dimensions for their new sports wheelchairs, and when these are delivered to be used, they often present some problem due to the lack of correct adaptation to the athlete's body. Therefore, the objective of this work was to develop and validate a customized wheelchair prescription equipment for racing, in addition to proposing the development of a model of racing wheelchair with some pieces developed by additive manufacture. This equipment is used to perform various measurements and adjustments according to ergo-anthropometric characteristics of the individual in such a way that it evaluates the best accommodation of the athlete to obtain the best performance with the propulsion in the wheelchair customized and optimized for this athlete according to the parameterization made using the prescription equipment. With this equipment it is possible to perform 14 of the main adjustments used for the prescription of a running wheelchair. The prescription equipment was designed and built according to safety and comfort requirements and has a robust and rigid structure for experimental testing on race tracks. The experimental tests carried out with participants who are not wheelchair users, and also with participants who are wheelchair users, allowed the equipment to be validated in terms of safety, comfort and prescription methodology. In parallel, a new protocol for automated evaluation of wheelchair racing in real time was implemented, which was validated and proposed the development of a new model of wheelchair racing in automated conditions.